Endovascular Treatment of Ruptured Renal Artery Aneurysm: A Case-Based Literature Review - Yub Raj Sedhai; Soney Basnyat; Tawseef Dar; Deepak Acharya (Case Reports in Medicine)
Renal artery aneurysms are extremely uncommon with a reported incidence of less than one percent in general population. They are being more frequently detected due to increasing availability and use of abdominal imaging. Renal artery aneurysm rupture is an extremely unusual cause of acute flank pain with hemodynamic instability. Given the rarity of diagnoses, clinicians may not consider and address this ruptured renal artery aneurysm early which can potentially lead to adverse clinical outcomes. We report the case of a 55-year-old male who presented with retroperitoneal bleeding from a ruptured aneurysm of the interlobular branch of renal artery. He was endovascularly treated with coil embolization. We have also reviewed the inherent literature.